(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Sustainable development is a concept focused on preserving current resources for them to be available to future generations as well, while at the same time fulfilling current human needs and facilitating adequate levels of development. Nowadays, there are many possible applications of sustainability principles, such as in the fields of the economy, agriculture, environment, energy, transport, architecture, and production. Sustainable production of materials and goods aims at improving the processes which are less damaging to the environment, which conserve natural resources and use low levels of energy, possibly derived from sustainable sources. One of the intensive energy- and resource-consuming industries is the conventional production of technical ceramics. Although non-toxic, ceramic waste is generated during the machining of the green bodies and is typically landfilled. To improve the sustainability of technical ceramics production, methods of recycling ceramic waste need to be developed and applied.